2019
DOI: 10.1186/s12987-019-0140-y
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic resistance of periarterial spaces in the brain

Abstract: Background Periarterial spaces (PASs) are annular channels that surround arteries in the brain and contain cerebrospinal fluid (CSF): a flow of CSF in these channels is thought to be an important part of the brain’s system for clearing metabolic wastes. In vivo observations reveal that they are not concentric, circular annuli, however: the outer boundaries are often oblate, and the arteries that form the inner boundaries are often offset from the central axis. Methods W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(119 citation statements)
references
References 43 publications
2
117
0
Order By: Relevance
“…According to Tithof et al [91], PVS are not concentric cylinders, but rather form ellipses around vessels to minimize resistance. This geometrical change along all vessels may decrease resistance by a factor of 2-3 [91], and thus likely increase PVS velocities by a similar factor in some of our models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Tithof et al [91], PVS are not concentric cylinders, but rather form ellipses around vessels to minimize resistance. This geometrical change along all vessels may decrease resistance by a factor of 2-3 [91], and thus likely increase PVS velocities by a similar factor in some of our models.…”
Section: Discussionmentioning
confidence: 99%
“…According to Tithof et al [91], PVS are not concentric cylinders, but rather form ellipses around vessels to minimize resistance. This geometrical change along all vessels may decrease resistance by a factor of 2-3 [91], and thus likely increase PVS velocities by a similar factor in some of our models. In addition, peak velocity in a concentric cylinder is double that of the mean velocity, which possibly may increase our velocity estimates in some of the models by another factor of approximately two.…”
Section: Discussionmentioning
confidence: 99%
“…The phase difference between the arterial wall velocity and the downstream fluid velocity (axial velocity, ) remained the same throughout the length of the domain. Flow resistance ( ) of a tube with an annular cross-section decreases with approximately the fourth power of the internal radius 26 .…”
Section: Peristaltic Pumping Requires Unphysiologically Large Amplitumentioning
confidence: 99%
“…We found that a very small pressure difference, 0.01 mmHg across the length of the PVS (5 mm), was sufficient to drive a mean downstream speed of 24.4µm/sec (Fig 4g), close to the mean flow speed observed in vivo 7 (Fig 4h). The pressure difference value was also found using equations derived in another recent theoretical study that estimated the flow resistance of paravascular spaces 26 . Such a small pressure difference is practically impossible to measure in live animals, due to the lack of instruments sensitive to such small changes 43,44 .…”
Section: Pressure Differences Not Arterial Pulsations Drive Bulk Flumentioning
confidence: 99%
See 1 more Smart Citation